The influence of superficial properties of ceramic-metal layers on acoustic emission - Бабак, В.П.; Філоненко, С.Ф.; Стадниченко, В.М. (Proceedings of National Aviation University (archive), 2005)
The influence of idle time on operational properties of friction pairs with ceramic-metal superficial layers is investigated in this article. The application of AE information for the control and diagnostics of complex tribotechnical systems directly during their operation is offered.